2023
DOI: 10.1371/journal.pgph.0002410
|View full text |Cite
|
Sign up to set email alerts
|

The politics of agricultural policy and nutrition: A case study of Malawi’s Farm Input Subsidy Programme (FISP)

Helen Walls,
Deborah Johnston,
Mirriam Matita
et al.

Abstract: The concept of food and nutrition policy has broadened from simply being an aspect of health policy, to policy interventions from across a wide range of sectors, but still with potentially important impact on nutritional outcomes. This wider and more complex conceptualisation involves policy with multiple objectives and stakeholder influences. Thus, it becomes particularly important to understand the dynamics of these policy processes, including policy design and implementation. To add to this literature, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 119 publications
0
2
0
Order By: Relevance
“…to the unaffordability of these diets, they are unable to do so. 10 Particularly as shown from the focus group discussions, these findings are likely due to population characteristics, as severely resource-constrained households with low incomes tend to focus on alleviating hunger, not dietary diversification. Furthermore, the level of ultra-processed food consumption among our study participants was low by international standards.…”
Section: Bmj Global Healthmentioning
confidence: 95%
See 1 more Smart Citation
“…to the unaffordability of these diets, they are unable to do so. 10 Particularly as shown from the focus group discussions, these findings are likely due to population characteristics, as severely resource-constrained households with low incomes tend to focus on alleviating hunger, not dietary diversification. Furthermore, the level of ultra-processed food consumption among our study participants was low by international standards.…”
Section: Bmj Global Healthmentioning
confidence: 95%
“… 9 Third, our qualitative analyses based on focus group discussions with men and women in these rural communities found that people are aware of needing to consume a great variety of (healthy) foods, and yet due to the unaffordability of these diets, they are unable to do so. 10 …”
mentioning
confidence: 99%